(untitled) (Fisioterapia e Pesquisa, 2006)
This study was designed to assess intratest reproducibility and inter-test reliability of clinical and radiographic Q angle measurements. Subjects were 20 women (40 knees), 21±5 years old, whose Q angles were measured by two clinical examiners and one radiographic tester. Both measurements were taken on subjects laying supine on the radiography table with a Ushaped foot stabilizer; each subject was instructed to keep leg muscles relaxed. Data collected were subject to statistical analyses ANOVA, intraclass correlation coefficient (ICC), and R test, significance being respectively set at 5%, >0.75, and >0.321. Results showed intratest p=0.44, intertests p=0.45, intratest ICC=0.81, intertests ICC=0.89 and R=0.42. These findings suggest the methodology here proposed to measure Q angle is reliable and reproducible; it may hence be used in clinical practice.